DNA extraction from Gallus gallus domesticus / Nurul Fitri Aida Ismal - Ismal, Nurul Fitri Aida (2016)
Domestic chicken (Gallus gallus domesticus) is one of the most important species for mankind due to economic and cultural significance. The purpose of the study is to extract and to determine the DNA molecule size of 25 µg liver tissue of Gallus gallus domesticus (chicken). The chicken liver was extracted using DNeasy Blood and Tissue kit that involved four major phase including lysis, washing, binding and elution in order to yield the DNA. By using gel electrophoresis, the sizes of DNA molecule can be determined by comparing with DNA marker. From the result, the visualization of extracted DNA was done on gel electrophoresis method under UV trans-illuminator by staining the DNA with a nucleic acid stain. By comparing to the DNA marker, the size of extracted genomic DNA from the liver of G. gallus domesticus is about 200 base pair (bp). The finding base pair in the G. gallus domesticus liver is successful and the extraction DNA ready to for PCR and other molecular biology applications without any additional purification.